Peregrinação e poesia : o espaço sagrado e o perfil feminino em cantigas de romaria - Rosa, Célia Santos da (2015)
The pilgrimage in Middle Age is of great importance for the literary and historic studies. Historically, several causes of pilgrimage are justified by faith, promises, hope for cure, penitence, among many others. In literary studies, the desire to make pilgrimage is registered in the cantigas d'amigo, specifically, in the cantigas de romaria, a typically Portuguese genre that, through verses, proposes two research hypotheses: the religious motive, close or distant, sincere or naughty, and the reason of the absence of the lover, who was away combating the moors in defense of the land. In that sense, the question which directs this work is the study of the sacred space of pilgrimage, besides the various reasons for its search in the cantigas de romaria. The present dissertation, named Pilgrimage and Poetry: The Sacred Space and the Female Profile in Cantigas de Romaria , besides studying the sacred space and the importance of pilgrimage also presents a study of the female profile in the selected corpus of the cantigas de romaria. With a bibliographic aspect, the study will be based on the theoretical concepts proposed by Blanchot, Duby, Huizinga, Le Goff, Saraiva e Lopes, Lapa, Maleval, Eliade, among others. The present study intends to contribute to the critic fortune of medieval poetry, specifically the cantigas de romaria.